Liquid crystal polymer, LCP fiber, preparation method and application thereof

By introducing -NH-groups into the liquid crystal polymer and reacting with the alkyl phosphate salt to form hydrogen bonds, the problem of insufficient interaction force between the LCP fiber and the resin matrix is ​​solved, the surface polarity and binding force of the LCP fiber are improved, and its mechanical properties and weather resistance are enhanced.

CN116836374BActive Publication Date: 2025-03-18ZHUHAI WANTONG SPECIAL ENG PLASTICS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310173317.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-28
Publication Date
2025-03-18
Estimated Expiration
2043-02-28

AI Technical Summary

Technical Problem

The interaction force between existing LCP fibers and resin matrix is ​​weak, which limits its application effect.

Method used

By introducing liquid crystal polymer monomer units with -NH-groups, the surface free energy of the liquid crystal polymer is improved, and the aqueous solution of alkyl phosphate salt is sprayed during the spinning process, so that the alkyl phosphate salt reacts with the amide group of the liquid crystal polymer to form hydrogen bonds, which are closely bound to the surface of the LCP fiber.

Benefits of technology

The surface polarity and binding force of LCP fibers are significantly improved, and the mechanical properties and weather resistance of LCP fibers are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The present invention provides a liquid crystal polymer, an LCP fiber, and a preparation method and application thereof, and belongs to the technical field of polymer materials. The monomer unit of the liquid crystal polymer of the present invention includes NH- and O- groups, and the molar content of the monomer unit containing NH- is 1 to 15%. The preparation method of the LCP fiber of the present invention uses the above-mentioned liquid crystal polymer as a raw material, sprays an alkyl phosphate ester salt aqueous solution during the spinning process, and the alkyl phosphate ester salt reacts with the amide group of the liquid crystal polymer to form a hydrogen bond, so that the alkyl phosphate ester salt is tightly combined with the LCP fiber, greatly improving the surface polarity of the LCP fiber, thereby improving the binding force between the LCP fiber and other resins.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a liquid crystal polymer, an LCP fiber, and a preparation method and application thereof. Background Art

[0002] Liquid crystal polymer fiber (LCP fiber) has excellent properties such as high strength, high modulus, moisture and heat resistance, weather resistance and good chemical resistance. It is often used as a reinforcing material and is applied in various fields such as aviation, military industry, and sports. However, due to the small number of chemically active groups on the surface of LCP fiber and low surface free energy, there is a defect of weak interaction with the resin matrix, which limits its application effect.

[0003] The modification methods of fiber surface can be divided into two categories: physical modification and chemical modification. Physical modification mainly includes ultrasonic impregnation modification, plasma modification, etc., while chemical modification mainly includes surface grafting, surface etching and coupling agent modification. At present, the research on the surface modification of LCP fibers is still in the stage of laboratory research. For example, Shi Weili et al. (Shi Weili, Wang Zhi, Wang Juan, et al. Chemical modification of the surface of thermotropic liquid crystal polyarylate fibers [J]. Synthetic Fibers, 2013 (11): 5.) reported a method for chemical modification of the surface of thermotropic liquid crystal polyarylate fibers. Epichlorohydrin was used as a treatment agent to modify the surface of LCP fibers by using Friedel-Crafts chemical reaction to improve the bonding strength with other resins; and Li Mengge from Donghua University (Li Mengge. Surface modification of thermotropic liquid crystal polyarylate fibers and study on their interfacial bonding properties with epoxy resin composites [D]. Donghua University, 2020.) reported the use of oxygen plasma combined with silane coupling agent to modify the surface of LCP fibers, thereby increasing the surface energy of the fibers and increasing the interfacial shear strength between the modified LCP fibers and the epoxy resin matrix from 5.18 MPa to about 10 MPa.

[0004] However, the current modification methods for LCP fibers are not only complex and time-consuming, but also require a subsequent cleaning process to remove residual reagents on the fiber surface, making it difficult to achieve industrialization; and the modification effect on LCP fibers is limited, and the interfacial shear strength between the fiber and the resin is still relatively low. Summary of the invention

[0005] The purpose of the present invention is to overcome the defect of weak interaction between LCP fiber and resin matrix in the prior art, and to provide a liquid crystal polymer, wherein the monomer unit includes -NH- and -O- groups, and the surface free energy of the liquid crystal polymer is increased to a certain extent by introducing -NH- groups.

[0006] Another object of the present invention is to provide a method for preparing the above-mentioned liquid crystal polymer.

[0007] Another object of the present invention is to provide a method for preparing LCP fiber, using the above-mentioned liquid crystal polymer as a raw material, spraying an alkyl phosphate ester salt aqueous solution during the spinning process, and the alkyl phosphate ester salt reacts with the amide group of the liquid crystal polymer to form hydrogen bonds, so that the alkyl phosphate ester salt is tightly combined with the LCP fiber, greatly improving the surface polarity of the LCP fiber, thereby improving the bonding force between the LCP fiber and other resins.

[0008] Another object of the present invention is to provide LCP fiber prepared by the above preparation method.

[0009] Another object of the present invention is to provide application of the above LCP fiber as a resin reinforcement material.

[0010] To achieve the above object, the present invention adopts the following technical solution:

[0011] A liquid crystal polymer comprising at least one of the monomer units represented by formula (1) and formula (2) and a monomer unit represented by formula (3):

[0012]

[0013] Wherein, R1, R2, and R3 are each independently selected from -NH- or -O-;

[0014] The molar content of the -NH-containing monomer unit is 1 to 15% based on the total molar amount of all monomer units constituting the liquid crystal polymer.

[0015] The monomer unit of the liquid crystal polymer of the present invention includes -NH- and -O- groups, wherein the amide group (-NH-) is a polar group, and the surface free energy of the liquid crystal polymer is increased by introducing a certain amount of amide groups.

[0016] In the subsequent processing of preparing LCP fibers from liquid crystal polymers, the amide group also reacts with alkyl phosphate salts to form hydrogen bonds, so that the alkyl phosphate salts are tightly bonded to the LCP fibers, further improving the surface polarity of the LCP fibers and increasing the bonding force between the LCP fibers and the resin.

[0017] When R1 is an -O- group, the monomer unit represented by formula (1) is derived from p-hydroxybenzoic acid; when R1 is an -NH- group, the monomer unit represented by formula (1) is derived from p-aminobenzoic acid.

[0018] When R2 is an -O- group, the monomer unit represented by formula (2) is derived from m-hydroxybenzoic acid; when R2 is an -NH- group, the monomer unit represented by formula (2) is derived from m-aminobenzoic acid.

[0019] When R3 is an -O- group, the monomer unit represented by formula (3) is derived from 2-hydroxy-6-naphthoic acid; when R3 is an -NH- group, the monomer unit represented by formula (3) is derived from 2-amino-6-naphthoic acid.

[0020] The inventors have found that the proportion of -NH-containing monomer units should not be too low or too high. Based on the total molar amount of all monomer units constituting the liquid crystal polymer, when the molar content of -NH-containing monomer units is less than 1%, the improvement in the free energy of the liquid crystal polymer is not obvious. When the molar content of -NH-containing monomer units is greater than 15%, the amide group is polar and easily forms hydrogen bonds, which easily causes the water absorption of the liquid crystal polymer to increase. When the water absorption of the liquid crystal polymer is high, the weather resistance of the LCP fiber decreases, which is not conducive to downstream applications. When it is mixed with the resin matrix as a resin reinforcing fiber, the binding force between the LCP fiber and the resin decreases. When the -NH-containing monomer unit is within the specified range of the present invention, the moisture absorption rate of the LCP fiber made of the liquid crystal polymer is below 0.2%.

[0021] Preferably, the molar content of the -NH- containing monomer unit is 5 to 10% based on the total molar amount of all monomer units constituting the liquid crystal polymer.

[0022] Preferably, the molar content of the monomer unit of formula (3) is 20 to 30% based on the total molar amount of all monomer units constituting the liquid crystal polymer.

[0023] Preferably, the molar content of the monomer unit of formula (2) is 1 to 10% based on the sum of the molar amounts of the monomer units of formula (1) and formula (2).

[0024] For liquid crystal polymers, the naphthalene ring content and benzene ring content in the monomer unit, as well as whether the substituent is in the meta position or the para position, will affect the melting point, crystallization temperature and shear viscosity of the liquid crystal polymer. In order to obtain LCP fibers with good processing performance and good mechanical properties, the melting point and shear viscosity of the liquid crystal polymer should not be too high or too low. The inventors have found that when the three monomer units of the present invention are in the above-mentioned molar percentage range, the melting point of the obtained liquid crystal polymer is 270-330°C, the crystallization temperature is 200-260°C, and the shear viscosity is 25-50 Pa·s. The melting point and shear viscosity are suitable, and the liquid crystal polymer has both good processing performance and mechanical properties.

[0025] The melting point and crystallization temperature of liquid crystal polymer are tested as follows:

[0026] The measurement was carried out using DSC 200F3 manufactured by NETZSCH Company: the temperature was increased from room temperature to 30°C above the melting point at a heating rate of 20°C / min, the temperature was then decreased to room temperature at 20°C / min, and finally the temperature was increased to 30°C above the melting point at 20°C / min; the melting point was obtained by taking the highest point of the melting peak of the second heating curve, and the crystallization temperature was obtained by taking the lowest point of the crystallization peak of the first cooling curve.

[0027] The shear viscosity of liquid crystal polymers is tested as follows:

[0028] The test was conducted using a Malvern capillary rheometer at a temperature of 20°C above the melting point and a shear rate of 1000s. -1 , measured using a die with an inner diameter of 1 mm and a length of 20 mm.

[0029] The present invention also protects a method for preparing the above-mentioned liquid crystal polymer, comprising the following steps:

[0030] Under inert gas pressure, the monomers corresponding to the monomer units shown in formula (1) to formula (3) are mixed and subjected to acylation reaction under the action of an acylating agent; the acylated product is then subjected to condensation reaction to obtain the liquid crystal polymer.

[0031] The liquid crystal polymer can be obtained by a conventional preparation method in the art by sequentially performing an acylation reaction and a polycondensation reaction.

[0032] Preferably, the pressurization condition is that the pressure is maintained at 0.1-0.2 MPa.

[0033] Preferably, the acylating agent is at least one of acetic anhydride, propionic anhydride, butyric anhydride, valeric anhydride, 2-ethylhexanoic anhydride, dichloroacetic anhydride, and difluoroacetic anhydride.

[0034] Preferably, the conditions for the acylation reaction are a reaction temperature of 100 to 180° C. and a reaction time of 30 minutes to 5 hours.

[0035] Preferably, the process of the polycondensation reaction is as follows: after the acylation reaction is completed, the pressure in the reactor is reduced to normal pressure, and the temperature is raised to 250-400° C. at a rate of 0.1-5° C. / min to discharge acetic acid and unreacted acetic anhydride molecules; when the acetic acid reception amount reaches more than 90% of the theoretical value, the pressure in the reactor is reduced to 0.1-10 kPa, and this reduced pressure condition is maintained for 10 min to 2 h.

[0036] Preferably, the acylation reaction and polycondensation reaction may also be carried out under the action of a catalyst.

[0037] The catalyst may be a conventional polyester polymerization catalyst.

[0038] Preferably, the catalyst is at least one of potassium acetate, sodium acetate, magnesium acetate, zinc acetate, antimony trioxide, and tetrabutyl titanate.

[0039] The present invention also protects a method for preparing LCP fiber, comprising the following steps:

[0040] S1. adding the liquid crystal polymer to a spinning device for spinning, melt plasticizing, extruding, and drawing, and spraying an alkyl phosphate salt aqueous solution during the drawing process to obtain a primary fiber;

[0041] S2. heat-treating the spun fibers obtained in step S1 to obtain the LCP fibers.

[0042] During the spinning process, the alkyl phosphate salt aqueous solution is sprayed, and the alkyl phosphate salt can adhere to the surface of the primary fiber. On the one hand, the alkyl phosphate salt can act as an oil to eliminate the static electricity and hair generated during the spinning process, and on the other hand, it can react with the amide group of the liquid crystal polymer to form a hydrogen bond. After the subsequent heat treatment process, the alkyl phosphate salt is closely combined with the LCP fiber, which greatly improves the surface polarity of the LCP fiber, thereby improving the binding force between the LCP fiber and other resins.

[0043] The inventors have found that other commonly used oils in fiber spinning, such as white oil, higher fatty acid esters, etc., are not suitable for the preparation of LCP fibers of the present invention. The oils will evaporate during the heat treatment stage, which can easily cause fiber adhesion and affect the mechanical properties of the fibers. At the same time, they cannot enhance the interfacial bonding force.

[0044] Preferably, in step S1, the alkyl phosphate salt attached to the surface of the spun fiber accounts for 0.1-1 wt.% of the spun fiber.

[0045] The adsorption amount of alkyl phosphate salt is tested according to the following method:

[0046] Spinning is carried out under the same process. A 10,000-meter-long fiber without spraying the alkyl phosphate ester salt aqueous solution is baked at 80°C for 3 hours, and its weight is m1. A 10,000-meter-long fiber sprayed with the alkyl phosphate ester salt aqueous solution is baked at 80°C for 3 hours, and its weight is m2. The adhesion amount of alkyl phosphate ester salt is (m2-m1) / m1.

[0047] The amount of alkyl phosphate salt attached to the surface of the primary fiber should not be too small, otherwise the polarity of the LCP fiber cannot be significantly improved; at the same time, the amount of attachment should not be too large, otherwise it may remain on the surface of the LCP fiber in a free state without forming hydrogen bonds with the amide group, affecting the interface bonding effect.

[0048] In order to achieve the above-mentioned appropriate attachment amount, preferably, the concentration of the alkyl phosphate ester salt in the alkyl phosphate ester salt aqueous solution is 1 to 5 wt.%.

[0049] Preferably, the alkyl phosphate salt has a structure shown in formula (4) and / or formula (5);

[0050]

[0051] Wherein, each M is independently selected from an alkali metal, and each R is independently selected from a C4 to C16 alkyl group.

[0052] Preferably, each M is independently selected from potassium or sodium.

[0053] Preferably, the alkyl phosphate salt is at least one of potassium dodecyl phosphate, potassium zinc phosphate, potassium di-tert-butyl phosphate, and sodium dodecyl phosphate.

[0054] Preferably, in step S1, the spinning equipment is a single screw extruder.

[0055] Preferably, in step S1, the stretching speed is 100-600 m / min.

[0056] Preferably, in step S1, the maximum spinning temperature is Tm-Tm+40°C, where Tm is the melting point of the liquid crystal polymer.

[0057] Preferably, in step S2, the heat treatment process is: treating at Tc-20℃~Tc+15℃ for 3~24h, and treating at Tm-30℃~Tm-10℃ for 3~48h; wherein Tc is the crystallization temperature of the liquid crystal polymer, and Tm is the melting point of the liquid crystal polymer; the heat treatment atmosphere is an oxygen-free atmosphere.

[0058] The present invention also protects an LCP fiber, comprising a base fiber and an alkyl phosphate salt, wherein the base fiber material comprises the liquid crystal polymer.

[0059] Preferably, in the LCP fiber, the alkyl phosphate salt accounts for 0.1-1 wt.% of the base fiber.

[0060] Preferably, the alkyl phosphate salt has a structure shown in formula (4) and / or formula (5);

[0061]

[0062] Wherein, each M is independently selected from an alkali metal, and each R is independently selected from a C4 to C16 alkyl group.

[0063] The present invention also protects the use of the above LCP fiber as a resin reinforcement material.

[0064] Compared with the prior art, the present invention has the following beneficial effects:

[0065] (1) The present invention provides a liquid crystal polymer, wherein the monomer unit includes -NH- and -O- groups, and the surface free energy of the liquid crystal polymer is increased by introducing amide groups.

[0066] (2) The present invention provides an LCP fiber and a preparation method thereof. The above-mentioned liquid crystal polymer is used as a raw material, and an alkyl phosphate ester salt aqueous solution is sprayed during the spinning process. The alkyl phosphate ester salt reacts with the amide group of the liquid crystal polymer to form hydrogen bonds, so that the alkyl phosphate ester salt is tightly combined with the LCP fiber, which greatly improves the surface polarity of the LCP fiber, thereby improving the bonding force between the LCP fiber and other resins. DETAILED DESCRIPTION

[0067] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form.

[0068] The sources of raw materials used in the embodiments and comparative examples of the present invention are as follows:

[0069] p-Hydroxybenzoic acid, m-hydroxybenzoic acid, p-aminobenzoic acid, 2-hydroxy-6-naphthoic acid, and 2-amino-6-naphthoic acid were purchased from Aladdin Reagents.

[0070] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. Unless otherwise specified, the reagents and materials used in the present invention are commercially available.

[0071] Examples 1 to 12, Comparative Examples 1 to 3

[0072] Examples 1 to 12 and Comparative Examples 1 to 3 respectively provide a liquid crystal polymer, and the preparation method is as follows:

[0073] Under nitrogen pressure, the pressure was maintained at 0.1-0.2 MPa, the monomers were mixed and added to the reactor according to Table 1, and the acylation reaction was carried out under the action of the acylating agent (acetic anhydride), the acylation reaction temperature was 140°C, and the reaction time was 2h;

[0074] After the acylation reaction is completed, the pressure in the reactor is reduced to normal pressure, and the temperature is raised to 250-400°C (40°C above the melting point of the liquid crystal polymer) at a rate of 1°C / min to discharge acetic acid and unreacted acetic anhydride molecules. When the acetic acid reception reaches more than 90% of the theoretical value, the pressure in the reactor is reduced to 4kPa, and this reduced pressure condition is maintained for 40 minutes to obtain a liquid crystal polymer.

[0075] Table 1 Monomer composition of the embodiments and comparative examples (molar percentage)

[0076]

[0077] After testing, the melting point, crystallization temperature and shear viscosity of the liquid crystal polymer are shown in Table 2.

[0078] Table 2 Test results of liquid crystal polymers

[0079]

[0080] Examples 13 to 30

[0081] Embodiments 13 to 30 provide a LCP fiber, respectively, and the preparation method is as follows:

[0082] S1. The liquid crystal polymer is added to a single screw extruder for spinning, melt plasticization, extrusion, drawing, and spraying an alkyl phosphate salt aqueous solution during the drawing process at a spraying rate of 2.5 g / min to obtain a primary fiber;

[0083] S2. The spun fiber obtained in step S1 is subjected to heat treatment, wherein the heat treatment process is 230°C for 6 hours, then heated to 250°C for 6 hours, and then 290°C for 6 hours to obtain LCP fiber;

[0084] The type of liquid crystal polymer, the drawing speed, the type and concentration of the alkyl phosphate ester salt, and the adhesion amount of the alkyl phosphate ester salt are shown in Table 3.

[0085] Table 3 Preparation parameters of LCP fibers of Examples 13 to 30

[0086]

[0087]

[0088] Comparative Examples 4 to 11

[0089] Comparative Examples 4 to 11 provide a LCP fiber, respectively, and the preparation method is as follows:

[0090] S1. Adding a liquid crystal polymer to a single screw extruder for spinning, after melt plasticization, extrusion, and drawing, spraying an alkyl phosphate salt aqueous solution or other oil during the drawing process, the spraying amount is 2.5g / min, to obtain a primary fiber;

[0091] S2. The spun fiber obtained in step S1 is subjected to heat treatment, wherein the heat treatment process is 230°C for 6 hours, then heated to 250°C for 6 hours, and then 290°C for 6 hours to obtain LCP fiber;

[0092] The type of liquid crystal polymer, the drawing speed, the type and concentration of the alkyl phosphate ester salt, and the adhesion amount of the alkyl phosphate ester salt are shown in Table 4.

[0093] Table 4 Preparation parameters of LCP fibers of comparative examples 4 to 11

[0094]

[0095] Performance Testing

[0096] The performance of the LCP fibers prepared in the examples and comparative examples was tested, and the specific method was as follows:

[0097] Fiber hair and broken wires: Use the chemical fiber cake appearance inspection system to inspect and observe whether there are hair and broken wires in 10,000 meters of fiber;

[0098] Fiber strength and fiber modulus: refer to standard ASTM C1557-20, measured by a universal tensile testing machine, the tensile speed is 50mm / min, each sample is measured 5 times, and the average value is taken;

[0099] Sample moisture absorption rate: Place the sample in a 50°C oven and dry for 24 hours, then cool it to room temperature in a dryer and weigh the sample to get m1; place the sample in a container filled with distilled water and control the water temperature at 23°C. After soaking for 24 hours, take out the sample and quickly wipe off the water on the surface of the sample with a clean dry cloth or filter paper, and weigh the sample to get m2. The sample moisture absorption rate is (m1-m2) / m1; measure 5 samples at the same time and take the average value;

[0100] Interfacial shear strength (IFSS): epoxy resin (HY-230) and epoxy curing agent were uniformly prepared at a mass ratio of 100:127, and kept at room temperature for 30 minutes. After the resin glue was in a viscous state, a needle was used to drop the viscous resin on the LCP fiber, so that the droplets embedded the LCP fiber and kept the droplets as spherical as possible (with a diameter of about 0.3mm). Then, the sample was placed in a 140℃ drying oven for 4 hours, and finally the sample was taken out and cooled to room temperature, and then the microsphere debonding test was performed; the clamping distance during the test was 2mm, the stretching speed is 10mm / min, the return speed is 150mm / min, the pre-tension is 0.05cN, and the interfacial shear strength is calculated according to the following formula: IFSS=F / πdL; wherein, F is the maximum pull-out force applied to a single fiber, d is the single fiber diameter, and L is the embedding length of the single fiber in the resin. For each LCP fiber, more than 15 embedded resin balls are prepared and their IFSS is tested, and the average value is calculated; the larger the IFSS, the stronger the bonding between the LCP fiber and the epoxy resin.

[0101] The test results of the embodiments are shown in Table 5, and the test results of the comparative examples are shown in Table 6.

[0102] Table 5 Test results of the embodiment

[0103]

[0104]

[0105] Table 6 Test results of comparative examples

[0106]

[0107] According to Comparative Examples 4, 6 and Examples 13 to 17, based on the total molar amount of all monomer units constituting the liquid crystal polymer, when the molar content of the -NH-containing monomer unit of the liquid crystal polymer is 1 to 15%, the mechanical properties and the binding force with the epoxy resin of the obtained LCP fiber are good; when the molar content of the -NH-containing monomer unit of the liquid crystal polymer is 0%, the polarity of the liquid crystal polymer is poor and the binding force with the epoxy resin is poor; when the content of the -NH-containing monomer unit in the liquid crystal polymer is too high, the moisture absorption rate is too high, and the binding force between the LCP fiber and the resin decreases.

[0108] According to the comparison between Example 18 and Example 13, the comparison between Example 19 and Example 17, and the test results of Examples 23 and 24, when the liquid crystal polymer contains a monomer unit represented by formula (2), and the molar content of the monomer unit of formula (2) is in the range of 1 to 10% based on the sum of the molar amounts of the monomer units of formula (1) and formula (2), the strength of the LCP fiber is relatively better, and the bonding force with the resin is relatively higher, indicating that the monomer unit represented by formula (2) is conducive to better overall performance of the LCP.

[0109] According to Comparative Example 5, when the monomer unit represented by formula (3) is not contained, the melting point of the liquid crystal polymer is too high, and the filaments are frequently broken during the spinning process, and continuous spinning is impossible, resulting in extremely poor processing performance.

[0110] According to Examples 15 and 25 to 27, different types of alkyl phosphates can react with the amide groups of the liquid crystal polymer to form hydrogen bonds, thereby increasing the surface polarity of the LCP fiber and improving the bonding force between the LCP fiber and the epoxy resin. From the test results of Comparative Example 7, when the alkyl phosphate is not sprayed, the bonding force between the LCP fiber and the epoxy resin is poor.

[0111] According to Examples 28 to 30 and Comparative Examples 8 to 9, the amount of alkyl phosphate salt attached to the surface of the spun fiber is in the appropriate range of 0.1 to 1 wt.%. The attachment amount should not be too small, because it cannot significantly improve the polarity of the LCP fiber and may cause the LCP fiber to break during production; at the same time, the attachment amount should not be too large, because it may remain on the surface of the LCP fiber in a free state without forming hydrogen bonds with the amide group, affecting the interface bonding effect.

[0112] According to Comparative Examples 10 and 11, when white oil or higher fatty acid ester is used as the oil, it is easy to cause fiber adhesion, which not only results in poor mechanical properties of the LCP fiber, but also fails to enhance the interfacial bonding force.

[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A LCP fiber, characterized in that: It comprises a base fiber and an alkyl phosphate salt, wherein the base fiber material comprises a liquid crystal polymer; The alkyl phosphate salt accounts for 0.1-1wt.% of the base fiber; The liquid crystal polymer comprises at least one of the monomer units represented by formula (1) and formula (2) and a monomer unit represented by formula (3): 、 、 ; Formula (1) Formula (2) Formula (3) Wherein, R1, R2, and R3 are each independently selected from -NH- or -O-; The molar content of the -NH-containing monomer unit is 1 to 15% based on the total molar amount of all monomer units constituting the liquid crystal polymer.

2. The LCP fiber according to claim 1, characterized in that: The molar content of the -NH--containing monomer unit is 5 to 10% based on the total molar amount of all monomer units constituting the liquid crystal polymer.

3. The LCP fiber according to claim 1, characterized in that: The molar content of the monomer unit of formula (3) is 20-30% based on the total molar amount of all monomer units constituting the liquid crystal polymer.

4. The LCP fiber according to claim 1, characterized in that: Based on the sum of the molar amounts of the monomer units of formula (1) and formula (2), the molar content of the monomer unit of formula (2) is 1-10%.

5. The LCP fiber according to claim 1, characterized in that: The preparation method of the liquid crystal polymer comprises the following steps: Under inert gas pressure, the monomers corresponding to the monomer units shown in formula (1) to formula (3) are mixed and subjected to acylation reaction under the action of an acylating agent; the acylated product is then subjected to condensation reaction to obtain the liquid crystal polymer.

6. The LCP fiber according to claim 1, characterized in that: The alkyl phosphate salt has a structure shown in formula (4) and / or formula (5); , ; Formula (4) Formula (5) Wherein, each M is independently selected from an alkali metal, and each R is independently selected from a C4~C16 alkyl group.

7. A method for preparing LCP fiber, characterized in that: The steps include: S1. Adding a liquid crystal polymer to a spinning device, melt-plasticizing, extruding, and drawing, spraying an alkyl phosphate salt aqueous solution during the drawing process to obtain a nascent fiber; S2. heat treating the spun fiber obtained in step S1 to obtain the LCP fiber; In step S1, the alkyl phosphate salt attached to the surface of the spun fiber accounts for 0.1-1 wt.% of the spun fiber; The liquid crystal polymer comprises at least one of the monomer units represented by formula (1) and formula (2) and a monomer unit represented by formula (3); 、 、 ; Formula (1) Formula (2) Formula (3) Wherein, R1, R2, and R3 are each independently selected from -NH- or -O-; The molar content of the -NH-containing monomer unit is 1 to 15% based on the total molar amount of all monomer units constituting the liquid crystal polymer.

8. The preparation method according to claim 7, characterized in that: The alkyl phosphate salt has a structure shown in formula (4) and / or formula (5); , ; Formula (4) Formula (5) Wherein, each M is independently selected from an alkali metal, and each R is independently selected from a C4~C16 alkyl group.

9. The preparation method according to claim 7, characterized in that: The alkyl phosphate salt is at least one of potassium dodecyl phosphate, potassium zinc phosphate, and potassium di-tert-butyl phosphate.

10. Use of the LCP fiber according to any one of claims 1 to 6 as a resin reinforcement material.

Citation Information

Patent Citations

  • Preparation system and method for aromatic thermotropic liquid crystal polymer

    CN109796584A

  • Stretchable liquid crystal polymer composition

    CN1491247A